2019
DOI: 10.1088/1367-2630/ab520e
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric twin-field quantum key distribution

Abstract: Twin-Field (TF) quantum key distribution (QKD) is a major candidate to be the new benchmark for far-distance QKD implementations, since its secret key rate can overcome the repeaterless bound by means of a simple interferometric measurement. Many variants of the original protocol have been recently proven to be secure. Here, we focus on the TF-QKD type protocol proposed by Curty et al (2019 NPJ Quantum Inf. 5 64), which can provide a high secret key rate and whose practical feasibility has been demonstrated in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 49 publications
(154 reference statements)
0
37
0
Order By: Relevance
“…One intuitive solution is to deliberately add fibers/losses to compensate for the shorter distance [19]. But this solution is not the optimal strategy, because it would increase signal loss and thus lower the secret key rate.Instead of physically adding fibres/losses, several recent theoretical papers [20][21][22][23] in TFQKD study the use of asymmetric intensities between Alice and Bob to compensate for channel asymmetry and obtain optical secret key rate 1 . Ref.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…One intuitive solution is to deliberately add fibers/losses to compensate for the shorter distance [19]. But this solution is not the optimal strategy, because it would increase signal loss and thus lower the secret key rate.Instead of physically adding fibres/losses, several recent theoretical papers [20][21][22][23] in TFQKD study the use of asymmetric intensities between Alice and Bob to compensate for channel asymmetry and obtain optical secret key rate 1 . Ref.…”
mentioning
confidence: 99%
“…[20,23] are based on an asymmetric-intensity version of the "Sending-or-not-Sending (SNS)" Protocol [9], while Refs. [21,22] are based on the protocol proposed in [11] by Curty, Azuma, Lo (for simplicity, let us call the protocol "CAL19" protocol here).In this paper we have implemented the protocol in Ref.[22] 2 . The key point of the protocol is that Alice and Bob can adjust 1 The limitation to symmetric optical channels has been first observed and investigated for MDIQKD, whose visibility also requires symmetry between optical channels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Note added-Recently, we found that [51,52] discussed the finite-key size effect and [53,54] discussed the security of TF-QKD under intensity fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…reducing the assumption on the devices) [9-14], but at the same time are also implementable with today's technology [15][16][17][18]. In this context, a protocol which recently received great attention is the Twin-Field (TF) QKD protocol originally proposed by Lucamarini et al [19], further developed to prove its security [20][21][22][23][24][25][26][27] and experimentally implemented [28][29][30][31]. Indeed, the TF-QKD protocol relies only on single-photon interference occurring in an untrusted node, making it a measurement-device-independent (MDI) QKD protocol capable of overcoming the repeaterless bounds [32,33].In a scenario where several users are required to share a common secret key, one can for instance perform bipartite QKD protocols between pairs of users and then use the secret keys established in this way to encode the final common secret key.…”
mentioning
confidence: 99%